2017
DOI: 10.18203/2349-3933.ijam20172259
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy retrospective study

Abstract: Background: Laparoscopic cholecystectomy is taken into account as a standard method of performing cholecystectomy and has substituted the old method throughout the world, while laparoscopic appendectomy still not attaining that reputation. In this paper, a retrospective study was done to compare between both laparoscopic and open appendectomy.Methods: Two hundred eighty-five patients were analyzed after appendectomy using either open or laparoscopic procedures. The data was compared over a period of 36 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Our results are in accordance with results obtained by [1,10,17] reported wound infection was more common after open appendectomy (20%) than laparoscopic appendectomy (4%). Similar results were obtained by [18,19] they concluded that LA was better than OA with respect to postoperative wound complications. The reduced incidence of wound infection is a major advantage of LA.…”
Section: Postoperative Complicationssupporting
confidence: 82%
“…Our results are in accordance with results obtained by [1,10,17] reported wound infection was more common after open appendectomy (20%) than laparoscopic appendectomy (4%). Similar results were obtained by [18,19] they concluded that LA was better than OA with respect to postoperative wound complications. The reduced incidence of wound infection is a major advantage of LA.…”
Section: Postoperative Complicationssupporting
confidence: 82%
“…Similarly a study conducted by Rbihat et al showed that the mean time for laparoscopic and OA group was 55 minutes and 22 minutes respectively with the duration of stay was two days in open surgery group whereas the laparoscopic group was only one day and 8 out of 159 had wound infection in OA group. 9 The study done by Vellani et al, the mean post-operative stay in days was relatively shorter for LA (1.97±2.3) compared to OA (3.1±1.8). The average time for the return of bowel movement was remarkably lesser for LA (10.6±8.2) hours than OA (21±13) hours.…”
Section: Resultsmentioning
confidence: 91%